Study of a Pd-Ag-Sb system alloy for metal-ceramics - Limkool P. (2014)
The present study is aimed at developing a palladium silver based alloy containing antimony and other elements for metal-ceramics. Composition 54.2Pd-36.2Ag-4.7Sb-2.9In-1.0Sn-1.0Ga++ + (alloy No. 10) was finally selected as the best for practical applications. Liquidus and solidus temperatures of this alloy were 1,250 degrees C and 1,087 degrees C. Under fired conditions, the Vickers hardness number, tensile strength, and elongation were 270, 647 MPa, and 3.4%, respectively. In the temperature range from 20 degrees C to 600 degrees C, the thermal expansion rate was 0.87%, and the thermal expansion coefficient was 15.0 X 10(-6)/degrees C. The mechanical and manipulation properties of this alloy were satisfactory for clinical applications.